2022
DOI: 10.1093/jbi/wbac080
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening and Outcomes Disparities Persist for Native American Women

Abstract: Over the past three decades, mortality rates from breast cancer have decreased for multiple racial groups but have remained constant for American Indian and Alaskan Native (AI/AN) women. Additionally, AI/AN women are less likely to receive timely breast cancer screening and are more likely to be diagnosed with advanced stage breast cancer at younger ages than their White counterparts. These disparities can be explained, in part, by the unique barriers to accessing care faced by AI/AN women. The Indian Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This is important for the trustworthy and ethical use of such AI technology, and an important finding in the context of recent concerns that AI may amplify health disparities 37 – 39 . Previous studies have shown disparities in the provision of breast cancer care related to race, ethnicity, and other demographic characteristics 40 43 . Here, an automated, objective method for breast density prediction could alleviate some of these disparities, for example, when assessing personalised cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for the trustworthy and ethical use of such AI technology, and an important finding in the context of recent concerns that AI may amplify health disparities 37 – 39 . Previous studies have shown disparities in the provision of breast cancer care related to race, ethnicity, and other demographic characteristics 40 43 . Here, an automated, objective method for breast density prediction could alleviate some of these disparities, for example, when assessing personalised cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other cancer types, breast cancer has the highest probability of being treated (around 90%). Cancer does not produce early pain, so it is not noticed until serious health issues arise [ 6 ]. Age is a factor in both breast cancer mortality and incidence rates.…”
Section: Introductionmentioning
confidence: 99%
“…AI/AN populations are entitled by treaty to receive healthcare free of charge provided by the US federal government, which for most is healthcare provided by the Indian Health Service (IHS). This universal health care coverage does not result in easily accessible health care services in many cases [ 12 ]. Challenges to health care access through the IHS stem from several factors including underfunding, geographic sparsity, and historic trauma leading to current mistrust [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This universal health care coverage does not result in easily accessible health care services in many cases [ 12 ]. Challenges to health care access through the IHS stem from several factors including underfunding, geographic sparsity, and historic trauma leading to current mistrust [ 12 ]. While AI/AN populations are entitled to healthcare, the federal funding is insufficient for addressing comprehensive healthcare needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation